Zur Synonymie von Geodromicus Redtenbacher (Coleoptera, Staphylinidae, Omaliinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1987)
Geodromicus Redtenbacher is considered to have priority over Psephidonus Gistel. Nomenclatural Acts Psephidonus Gistel, 1856 (Staphylinidae), syn. n. of Geodromicus Redtenbacher, 1856 [24. ix.]